Evaluating healthcare professionals’ perceptions of dispensing separation and sale of pharmacy medicine in Brunei Darussalam - Juperi, Rabi'atul Nur Amalia Abdullah; Goh, Hui Poh; Rehman, Inayat Ur; Lee, Kah Seng; Long, Chiau Ming *; Hermansyah, Andi (Taylor and Francis Group, 2023)
Background: Pharmacy medicine (P) is obtained exclusively from a pharmacy under the supervision of a pharmacist. This study aims to understand the perception of healthcare professionals towards the dispensing separation, as well as the dispensing of pharmacy medicine by community pharmacies to enhance patient health outcomes in Brunei Darussalam.